21st-century liberal democracy and its contradictions - Bellini, Paolo (2014)
This brief paper intends to highlight the contradictions in which liberal democracy struggles within the process of globalisation, influenced as it is by the new connecting technologies. In particular, the difficult relationship between liberalism and democracy is analysed in light of the latest communitarist theories and new trends that interpret them socially.